(untitled) (Research, Society and Development, 2022)
The objective was to evaluate the use of green solvents in the extraction of phenolic compounds from avocado peel. 7 solvents were tested: 1) ethanol (100%); 2) ethanol (50%) + distilled water (50%); 3) distilled water (100%); 4) lactic acid (100%); 5) lactic acid (50%) + distilled water (50%); 6) glycerin (100%); 7) glycerin (50%) + distilled water (50%). For the tests, approximately 5 grams of avocado peel and 100 mL of the tested solvent were used. For the extraction of total phenolic compounds, water + glycerin (50%) had the highest extraction potential with 609.9 mg EAG/L, with a variation of approximately 45% in relation to the solvent with the lowest yield (333.9 mg EAG/L) obtained with 100% ethanol. For DPPH, ethanol (100%); lactic acid (100%) and lactic acid (50%) + water (50%); showed statistical difference (p<0.05) from the other solvents. Lactic acid (100%) and lactic acid (50%) + water (50%) had highest values ​​(1.156 mg EAG/L), followed by ethanol (100%) with 1.129 mg EAG/L. However, ethanol (50%), glycerin (50%), water (100%), ethanol (100%) and lactic acid (50%) showed better performance in the stability of the ABTS+ radical. Thus, it can be concluded that 50% glycerin is more suitable for extracting phenolic compounds from avocado peel and also for evaluating the antioxidant activity using the ABTS and DPPH method. The interaction between extraction time and solvent has an effect on the proportion of extracted compounds, and 50% glycerin showed better results for the extraction of phenolic compounds present in avocado peel.